PEMANFAATAN BUAH MENGKUDU DAN JAHE MERAH DALAM PEMBUATAN BUBUK INSTAN - Hedi Irawan; Yusmarini Yusmarini; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to get the best ratio between noni and red ginger for making instan powder which was preferred instant by panelists and fulfilled standard instan powder. This research Completely Randomized Design (CRD) with five treatments and three replications which followed by Duncan’s New Multiple Range Test (DNMRT) at 5%. The Treatment were MJ1 (noni 10 g and red ginger 90 g), MJ2 (noni 20 g and red ginger 80 g), MJ3 (noni 30 g and red ginger 70 g), MJ4 (noni 40 g and red ginger 60 g) and MJ5 (noni 50 g and red ginger 50 g). The result of this research showed that the combination of noni and red ginger gave significant effect on water content, ash content, sucrose content, and organoleptic test. The best treatment  was MJ2 whichhad water content 1.14%; ash content 0.46% and sucrose  content 73.95%, with description colour grey to brown, flavour ginger and instan powder drink had colour yellow to brown, flavour ginger, taste ginger and overall assesment of instant powder. Keywords: Instant powder, red ginger and noni